A Photoswitchable Colorimetric Sensor for Fluoride Based on a Dithienylethene Unit. (June 2018) - Li, Ziyong; Zhang, Honglin; Zhang, Haining; Xie, Yanfu; Chen, Hong; He, Chaojun; Wang, Yangyang; Ya, Huiyuan; Guo, Hui
A novel dithienylethene amide-based photoswitchable anion receptor was synthesised by amidation of 4, 4′-(cyclopent-1-ene-1, 2-diyl) bis(5-methylthiophene-2-carboxylic acid) with 4-nitroaniline in 56% yield under mild conditions; its structure was confirmed by NMR, MS and elemental analysis. Investigation of its photochromic properties indicated that 4, 4′-(cyclopent-1-ene-1, 2-diyl)bis[5-methyl-N-(4-nitrophenyl) thiophene-2-carboxamide] had good reversibility and excellent fatigue resistance upon irradiation with UV or visible light and can serve as a colorimetric sensor for fluoride, resulting in a significant change in the absorption spectrum.